Identification of Alzheimer's EEG With a WVG Network-Based Fuzzy Learning Approach - Yu, Haitao; Zhu, Lin; Cai, Lihui; Wang, Jiang; Liu, Jing; Wang, Ruofan; Zhang, Zhiyong (Frontiers in Neuroscience, 2020)
In this paper, we propose a novel method based on fuzzy learning and complex network for identification of Alzheimer's disease (AD) with electroencephalograph (EEG) signals. Weighted visibility graph (WVG) algorithm is first applied to transform each channel EEG into network and its topological parameters were further extracted. Statistical analysis indicates that AD and normal subjects show significant difference in the structure of WVG network and thus can be used to identify Alzheimer's disease. Taking network parameters as input features, a Takagi-SugenoKang(TSK) fuzzy model is established to identify AD's EEG signal. Three feature sets, single parameter from multi-networks, multi-parameters from single network, and multi-parameters from multi-networks, are considered as input vectors respectively. The number and order of input features in each set is optimized with various feature selection methods. Classification results demonstrate the ability of network-based TSK fuzzy classifiers and the feasibility of three input feature sets. The highest accuracy can achieve 95.28% for single parameter from four networks, 93.41% for three parameters from single network. In particularly, multi-parameters from multi-networks set can obtained best result. The highest accuracy 97.12% is achieved with five features selected from four networks. The combination of network and fuzzy learning can highly improve the efficiency of AD's EEG identification.